αA-Crystallin Mediated Neuroprotection in the Retinal Neurons Is Independent of Protein Kinase B - Nath, Madhu; Fort, Patrice Elie (Frontiers in Neuroscience, 2022)
Phosphatidylinositol 3-kinase (PI3K)/Akt signal pathway mediates pro-survival function in neurons. In the retina, PI3K/AKT/mTOR signaling pathway is related to the early pathogenesis of diabetic retinopathy. Signaling molecules in the membrane-initiated signaling pathway exhibiting neuroprotective function interacts with the PI3K/Akt pathway as an important survival pathway. Molecular chaperone α-Crystallins are known to potentially interact and/or regulate various pro-survival and pro-apoptotic proteins to regulate cell survival. Among these demonstrated mechanisms, they are well-reported to regulate and inhibit apoptosis by interacting and sequestrating the proapoptotic proteins such as Bax and Bcl-Xs. We studied the importance of metabolic stress-induced enhanced Akt signaling and αA-crystallin interdependence for exhibiting neuroprotection in metabolically challenged retinal neurons. For the first time, this study has revealed that αA-crystallin and activated Akt are significantly neuroprotective in the stressed retinal neurons, independent of each other. Furthermore, the study also highlighted that significant inhibition of the PI3K-Akt pathway does not alter the neuroprotective ability of αA-crystallin in stressed retinal neurons. Interestingly, our study also demonstrated that in the absence of Akt activation, αA-crystallin inhibits the translocation of Bax in the mitochondria during metabolic stress, and this function is regulated by the phosphorylation of αA-crystallin on residue 148.